2021
DOI: 10.15252/embj.2021108080
|View full text |Cite
|
Sign up to set email alerts
|

SNX10‐mediated LPS sensing causes intestinal barrier dysfunction via a caspase‐5‐dependent signaling cascade

Abstract: Altered intestinal microbial composition promotes intestinal barrier dysfunction and triggers the initiation and recurrence of inflammatory bowel disease (IBD). Current treatments for IBD are focused on control of inflammation rather than on maintaining intestinal epithelial barrier function. Here, we show that the internalization of Gram-negative bacterial outer membrane vesicles (OMVs) in human intestinal epithelial cells promotes recruitment of caspase-5 and PIKfyve to early endosomal membranes via sorting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In addition, knocking out SNX10 using CRISPR/Cas9 or treating with the SnX10 inhibitor DC-SX029 blocks LPS release, caspase-5 activation, and downstream signaling, effectively alleviating intestinal barrier dysfunction induced by E. coli BL21 EVs. 119 Although the E. coli BL21 used in this study is not a typical strain in the host gut, these findings are significant for research on IBD pathogenesis. Apart from LPS, GBEVs secreted by some enteropathogenic bacteria contain protein hydrolases.…”
Section: Gbevs-mediated Bacteria-host Interactionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, knocking out SNX10 using CRISPR/Cas9 or treating with the SnX10 inhibitor DC-SX029 blocks LPS release, caspase-5 activation, and downstream signaling, effectively alleviating intestinal barrier dysfunction induced by E. coli BL21 EVs. 119 Although the E. coli BL21 used in this study is not a typical strain in the host gut, these findings are significant for research on IBD pathogenesis. Apart from LPS, GBEVs secreted by some enteropathogenic bacteria contain protein hydrolases.…”
Section: Gbevs-mediated Bacteria-host Interactionsmentioning
confidence: 94%
“…Wang et al incubated E. coli BL21 EVs with Caco-2, HT-29, and NCM460 cells, and found that GBEVs reduced E-cadherin expression in cells in a concentration-dependent manner. 119 The team further found that internalization of E. coli BL21 EVs by IECs promotes the recruitment of caspase-5 and PIKfyve (involved in endosome maturation) to early endosomal membranes by sorting nexin 10 (SNX10, a member of the SNX family proteins), while promoting the release of LPS from GBEVs into the cytosol. Activated caspase-5 also leads to the phosphorylation of Lyn, the upstream regulator of Snail/Slug, which promotes nuclear translocalization of Snail/Slug and downregulates E-cadherin expression, ultimately leading to intestinal barrier dysfunction.…”
Section: Gbevs-mediated Bacteria-host Interactionsmentioning
confidence: 99%
“…However, in the context of IBD the differential contributions of caspase-4 and -5 to inflammatory and other pathological events are not clear. Recently, Wang et al proposed that caspase-5 may contribute to intestinal barrier dysfunction, rather than pyroptosis, during IBD ( Wang et al, 2021 ). Sorting nexin 10 (SNX10) was shown to facilitate cytosolic release of LPS from OMVs by recruiting caspase-5 to the endosomal membrane.…”
Section: Mechanisms Enhancing Lps-mediated Activationmentioning
confidence: 99%
“…Sorting nexin 10 (SNX10) was shown to facilitate cytosolic release of LPS from OMVs by recruiting caspase-5 to the endosomal membrane. Caspase-5 is reported to facilitate the down regulation of E-cadherin expression in a process dependent on Lyn phosphorylation and activation of Snail/Slug transcription factors ( Wang et al, 2021 ). Furthermore, knockdown or inhibition of SNX10 rescued OMV-induced barrier dysfunction and DSS-induced colitis symptoms in mice ( Wang et al, 2021 ).…”
Section: Mechanisms Enhancing Lps-mediated Activationmentioning
confidence: 99%
See 1 more Smart Citation